Reproducibility of biomedical research – The importance of editorial vigilance - Bustin, Stephen A. (Biomol Detect Quantif, 2017)
Many journal editors are a failing to implement their own authors’ instructions, resulting in the publication of many articles that do not meet basic standards of transparency, employ unsuitable data analysis methods and report overly optimistic conclusions. This problem is particularly acute where quantitative measurements are made and results in the publication of papers that lack scientific rigor and contributes to the concerns with regard to the reproducibility of biomedical research. This hampers research areas such as biomarker identification, as reproducing all but the most striking changes is challenging and translation to patient care rare.